The Role of Principal’s Leadership in Improving the Quality of Mathematics Education at Junior High School Kembang Tanjong - Hery Saputra; Cut Italina (Junal Ilmu Manajemen, 2020)
The success of an educational institution is highly dependent on the contribution and the role of a leader, who then commonly called the principal who should be able to bring its institutions towards achieving the goals set, able to see the changes and be able to see the future in globalization that is now significantly better life.The problem of this research is how the leadership's effect in improving the quality of mathematics education and how the principal's role in improving the quality of mathematics education at SMPN 1 Kembang Tanjong. The objective of this research is to measure and analyze the effect of principal’ leardership in improving the quality of mathematics education and the role of principal’s leadership in improving the quality of mathematics education. The method used in this research is qualitative descriptive method, in which the writer describes how the effects of principal in improving the quality of Islamic education at SMPN 1 Kembang Tanjong. The sample of this research is one principals, one vice principal, three teachers, two student, one society and one committee with technique of documentation, observation, and interviews with principals and teachers. The data analysis was done by means of: data reduction, data presentation, and conclusion. The results showed that the effect of school principals at SMPN 1 Kembang Tanjong towards improving the quality of education is guiding, developing, motivation and supervis